Pontoppidan og rabbinerens datter - Loft Nielsen, Henrik (Pontoppidaniana, 2025)
Abstract In 1918, Henrik Pontontoppidan published a small text based on a holiday memoir. It is called The Priest´s Daugther and is about a young orthodox Jewish girl, who wants to spend her summer holiday at a seaside hotel in Blokhus, Denmark. It is not a success, she does not fit in and has to go back to her family before time. In this article, Henrik Loft Nielsen traces the story back to the summer of 1887, when Pontoppidan spent a prolonged holiday in Blokhus at the same time as a young Jewish girl from his native town, Randers. Loft Nielsen tells the girl´s story up to its sad ending in 1891. On this holiday, Pontoppidan also met another young woman, Antoinette Kofoed, who was to become his second wife later. She too plays a part in the story. In 1930 the short story was republished in a rewritten form and with the title The Rabbi´s Daugther.